Nilai Educational Parenting dalam Surah Lukman Ayat 12 - 19 serta Relevansinya dengan Penguatan Pendidikan Karakter - Muzammil Muzammil; Yazid Albustomi (PALAPA, 2022)
Character education is a plus character education, which involves aspects of knowledge, feelings, and action. The focus of the research in this study is to find out and describe more deeply on the value of parental education and the value of character education contained in the story of Luqman al-Hakim in the letter Luqman verses 12-19. The research method used in this research is library research. The values of parenting education contained in the letter Luqman verses 12-19 are gratitude, being wise, doing good deeds, being respectful, being friendly, being patient, and being humble. Meanwhile, the relevance of religious character with parenting education is the cultivation of a sense of faith so that it is not affected by anything. While the nationalist character is able to prioritize the interests of the nation rather than personal interests. Independent character is a behavior or attitude that is used fully and to achieve all of his hopes, ideals, and dreams without dependence on others. The character of Integrity is based on efforts to produce himself as a person who can always be trusted in words and actions. The character of mutual assistance is an activity that will be carried out together by one group or individual using having to be actively or passively involved in it.